ڕاپەڕینی ١٢ی ئاداری ٢٠٠٤ لە ڕۆژئاوای کوردستان توێژینەوەیەکی مێژوویی-سیاسییە - عبداللە, پ. ی. د. هاوار کمال میرزا; عبدالقادر, خوێندکاری ماستەر: ئاوات عبداللە (Sulaimani Journal for Humanities, 2023)
The beginning of Bashar al-Assad's coming to power and his promise of more freedom under the name of the Damascus Spring was a golden opportunity for the Kurds, but the government feared that the Kurds would take advantage of the situation. It made the government regret it and even acted harsher against the Kurds than ever before. Repressive behavior, considering the Kurds as foreigners and strict security surveillance, etc., caused the explosion of the Kurdish situation in the West and led to the failure of the March 12, 2004 uprising. This research uses a political historical methodology to chronologically analyze the events of March 12, 2004 and their consequences on the Western Kurds. The first topic focuses on the situation of the Kurds in West Kurdistan from the coming to power of Bashar al-Assad until the second topic discusses the causes and how the uprising in Qamishli on March 12, 2004 and the position of the Syrian government towards the uprising. The third topic is devoted to presenting the consequences of the 2004 uprising in West Kurdistan and highlighting the attitudes and reactions to the situation. Finally, the results are briefly presented.